Pin1 Promotes Regulated Necrosis Induced by Glutamate in Rat Retinal Neurons via CAST/Calpain2 Pathway - Wang, Shuchao; Liao, Lvshuang; Wang, Mi; Zhou, Hongkang; Huang, Yanxia; Wang, Zhen; Chen, Dan; Ji, Dan; Xia, Xiaobo; Wang, Yong; Liu, Fengxia; Huang, Jufang; et al. (Frontiers in Cellular Neuroscience, 2018)
The purpose of the current study was to investigate whether peptidyl-prolyl cis/trans isomerase NIMA-interacting 1 (Pin1) can interact with calpastatin (CAST) and regulate CAST/calpain2, under excessive glutamate conditions, and subsequently regulate necrosis in rat retinal neurons. Glutamate triggered CAST/calpain2-mediated necrosis regulation in primary cultured retinal neurons, as demonstrated by propidium iodide-staining and lactate dehydrogenase assay. Co-IP results and a computer simulation suggested that Pin1 could bind to CAST. Western blot, real-time quantitative polymerase chain reaction, immunofluorescence, and phosphorylation analysis results demonstrated that CAST was regulated by Pin1, as proven by the application of juglone (i.e., a Pin1 specific inhibitor). The retinal ganglion cell 5 cell line, combined with siRNA approach and flow cytometry, was then used to verify the regulatory pathway of Pin1 in CAST/calpain2-modulated neuronal necrosis that was induced by glutamate. Finally, in vivo studies further confirmed the role of Pin1 in CAST/calpain2-modulated necrosis following glutamate excitation, in the rat retinal ganglion cell and inner nuclear layers. In addition, a flash electroretinogram study provided evidence for the recovery of impaired visual function, which was induced by glutamate, with juglone treatment. Our work aims to investigate the involvement of the Pin1-CAST/calpain2 pathway in glutamate-mediated excitotoxicity.